Altitudinal Impact on Phytochemical Composition and Mycorrhizal Diversity of Taxus Contorta Griff in the Temperate Forest of Shimla District - Chauhan, Saurav; Dhalaria, Rajni; Ghoshal, Shankharoop; Kanwal, K S; Verma, Rachna (Journal of basic microbiology, 2024)
Taxus contorta (family Taxaceae) is a native plant of temperate region of western Himalaya. The current study investigated the effect of altitude on the phytochemical composition and mycorrhizal diversity, associated with distribution of T. contorta in Shimla district, Himachal Pradesh, India. Quantitative phytochemical analysis of the leaf extracts indicated that alkaloid levels decreased with altitude, with the highest value in Himri's methanol extracts (72.79 ± 1.08 mg/g) while phenol content increased with altitude, peaking in Nankhari's methanol extracts (118.83 ± 5.90 mg/g). Saponin content was higher in methanol extracts (78.13 ± 1.66 mg/g in Nankhari, 68.06 ± 1.92 mg/g in Pabbas, and 56.32 ± 1.93 mg/g in Himri). Flavonoid levels were notably higher in chloroform extracts, particularly in Nankhari (219.97 ± 2.99 mg/g), and positively correlated with altitude. Terpenoids were higher in chloroform extracts at Himri (11.34 ± 0.10 mg/g) and decreased with altitude. Taxol content showed minimal variation between solvents and altitudes (4.53-6.98 ppm), while rutin was only detected in methanol extracts (1.31-1.46 ppm). Mycorrhizal spore counts in T. contorta's rhizosphere varied with altitude: highest at Himri (77.83 ± 2.20 spores/50 g soil), decreasing to Pabbas (68.06 ± 1.96 spores/50 g soil) and lowest at Nankhari (66.00 ± 2.77 spores/50 g soil), with 17 AMF species identified overall, showing significant altitudinal influence on spore density. The rhizosphere of T. contorta was shown to be dominated by the Glomus species. The rhizospheric soil of the plant was found to be slightly acidic. Organic carbon and available potassium content decreased contrasting with increasing available nitrogen and phosphorus with altitude. Correlation data showed strong negative links between organic carbon (-0.83), moderate positive for nitrogen (0.46) and phosphorus (0.414), and moderate negative for potassium (-0.56) with the altitude. This study provides a comprehensive insight into changes in phytochemical constituents, mycorrhizal diversity and soil composition of T. contorta along a range of altitude.
Keywords: flavonoidy; Plant Leaves; Flavonoids; Plant Extracts; Alkaloids; terpeny; alkaloidy; Indie; saponiny; tis; Forests; lesy; Soil Microbiology; canonical correspondence analysis; rostlinné extrakty; fytonutrienty; listy rostlin; Terpenes; Saponins; kořeny rostlin; biodiverzita; Altitude; Mycorrhizae; půdní mikrobiologie; India; Taxus; mycorrhiza; Plant Roots; mykorhiza; phytochemicals; temperate forest; Phytochemicals; nadmořská výška; Biodiversity